Teacher Talk: The Use of L1 vs. L2 in the Classroom - Margaretha Dharmayanti Harmanto (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
Teacher talk is one of the aspects in second language acquisition in which the teacher talk functioned as the input for the learners. Besides providing input for the learners, teacher talk provides interaction in the classroom. The teacher talk in this study aims to discover the overall approach of the English lecturers to use Bahasa Indonesia (L1) and English (L2) in the classroom. The data of the study was gathered from the questionnaires and interview. The participants of the research were the lecturers of Language Training Center, Universitas Muhammadiyah Yogyakarta. The result findings show that the use of L2 is still dominant for each category in the discourse assessed through the questionnaires.